Acara Penggabungan Perkara Gugatan Ganti Rugi dalam Undang-Undang Nomor 31 Tahun 1997 Tentang Peradilan Militer - Parluhutan Sagala; Agustono Agustono; Irman Putra; Arief Fahmi Lubis (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. Viewed from the perspective of law enforcement, with the rarity of filing a claim for compensation or a request to merge a claim for compensation, it requires careful research because after all the core of law enforcement is upholding rights and carrying out obligations. The purpose of this study is to show that the use of the right to claim compensation or a request for compensation is very rare. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research was conducted. The results of this study indicate that the method of claiming compensation can be done by merging a claim for compensation in a criminal case, through unlawful acts and through a request for restitution.